2015
DOI: 10.3390/socsci4030546
|View full text |Cite
|
Sign up to set email alerts
|

Reconceptualising the Gender of Fitness Doping: Performing and Negotiating Masculinity through Drug-Use Practices

Abstract: Abstract:This article analyses self-portrayals and gender constructions among Swedish male bodybuilders who are engaged in fitness doping. The empirical material comes from a larger ethnographic investigation into gym culture. The results show that there is a strong propensity to conform with particular gender fantasies that rests heavily on a binary understanding of gendered, doped bodies. However, this storyline does not apprehend the entire self-presentation of the analysed drug users. Negotiations and incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Our results could also have captured a group of young adult males who focus on physical appearance and engage in partying and risk behaviors, comparable to the gay men in the gym studies discussed above. It has been suggested that drug use practices and weight training in a male “body subculture” can be understood as a way to construct a masculine identity and to achieve an idealized male body [ 41 ]. Our estimates were higher than the estimates in a study of anabolic substance use among 611 visitors to German fitness centers, where 15.9% reported using other illicit drugs [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results could also have captured a group of young adult males who focus on physical appearance and engage in partying and risk behaviors, comparable to the gay men in the gym studies discussed above. It has been suggested that drug use practices and weight training in a male “body subculture” can be understood as a way to construct a masculine identity and to achieve an idealized male body [ 41 ]. Our estimates were higher than the estimates in a study of anabolic substance use among 611 visitors to German fitness centers, where 15.9% reported using other illicit drugs [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Being part of the larger umbrella project, a total of thirty-two (26 men, 6 women) bodybuilders and dedicated gym-goers with fitness doping experiences were interviewed on at least two occasions. In this paper we focus on the data gathered from the interviews with the six female participants, as the interview material concerning male experiences has been analysed elsewhere (Andreasson and Johansson 2014;Andreasson 2015). The oldest woman interviewed was 47, the youngest 21.…”
Section: Methods and Methodologymentioning
confidence: 99%
“…Therefore, we can safely say that in a Swedish context since the 1990s PIED use has been viewed as a public health issue and societal problem. As such, doping has primarily been discussed in relation to young men's muscular masculinities, particularly in public discourse (Andreasson 2015). Although acceptance of extreme bodies and different ways of 'doing gender' are more common in public discourse today, women's fitness doping practices have been marginalized not only due to effects of the Swedish Doping Act but to gendered expectations attached to the practice.…”
Section: Pied Use the Law And The Other Gendermentioning
confidence: 99%
“…First, we have the issue of a physical activity background. Although the participants' commencement of drugs use varies and research usually distinguishes between doping in sport versus society generally, it can be noted that all participants in this study had been involved in some sort of organized sport when younger (see also, Andreasson, 2103Andreasson, , 2015. Initially, it was Nick's desire to achieve better results in boxing that led him to the gym, and over a 5-year period, his interest in boxing decreased while his interest in having a nicelooking body took off, eventually leading him into the use of steroids.…”
Section: Approaching Dopingmentioning
confidence: 99%
“…As a means of stressing the contextual differences between these spheres and cultural contexts, terms such as “vanity doping,” “fitness doping,” “recreational doping,” and the use of “image-enhancing drugs” have sometimes been employed in the fitness context (see, for example, Thualagant, 2012). In order not to predetermine the motives that lie behind different pathways to (and from) doping, in this article we will employ the term fitness doping , emphasizing the context of the form of doping in question rather than trying to pinpoint the motives behind it (see also Andreasson, 2015).…”
mentioning
confidence: 99%